THE DETERMINANTS OF TAXPAYERS’ PERCEPTION ON THE ETHICS OF TAX EVASION : STUDY ON THE CORPORATE TAXPAYERS REGISTERED AT THE SMALL TAX OFFICE OF SURABAYA RUNGKUT) - Try Zuliyanti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims at identifying the determinants of taxpayers’ perception on the ethics of tax evasion. The primary data are obtained from questionnaires distributed to 123 corporate taxpayers registered at the Small Tax Office of Surabaya Rungkut. The samples are selected by convenience sampling method. The hypothesis is analyzed using Partial Least Square (PLS) with SmartPLS. The result of analysis show that tax compliance and tax system influence the taxpayers’ perception on the ethic of tax evasion; whereas fairness, discrimination, and tax audit do not affect affect their perceptions on the ethics of tax evasion.Keyword: Fairness, Discrimination, Tax compliance, Tax audit, Tax system